Graphene oxide GO / hydroxyapatite HA / IL-4 implant coating as well as preparation method and application thereof
By constructing graphene oxide GO/hydroxyapatite HA/IL-4 implant coating on the implant surface, the problems of insufficient bone binding and immune response of existing implant materials were solved, and a higher implant success rate and faster healing process were achieved.
Patent Information
- Application Number
- CN202411940010.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
Existing implant materials such as pure titanium and its alloys are insufficient in vivo bone binding, resulting in loosening and falling off of the implant, affecting the long-term repair effect. At the same time, titanium ions may trigger an immune response, limiting their indications and success rate.
Graphene oxide GO/hydroxyapatite HA/IL-4 implant coating was used to build a composite coating with sustained release IL-4 on the titanium surface by electrochemical methods, which promotes bone differentiation of bone marrow stem cells and polarization of macrophages, and enhances the binding of implants and bones.
It improves the speed and quality of bone binding formation in the body, expands the indications of the implant, improves the success rate, and shortens the treatment process and healing time.
Smart Images

Figure CN119770718A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of implant coatings, and relates to implant coatings and preparation methods and applications thereof, and specifically relates to a graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method and application thereof. Background Art
[0002] Tooth loss is one of the most important diseases in clinical oral medicine. The rapid economic development, improved living standards, population growth and aging have led to a sharp increase in demand for dental implants. The loss of natural teeth affects the patient's facial appearance, and is not conducive to oral pronunciation, chewing and language functions, causing digestive and oral system disorders, and even causing serious psychological problems in patients.
[0003] Although implant technology is becoming more and more mature, it is not uncommon for pure titanium implants to fail clinically due to insufficient bone integration, and secondary surgical intervention brings great pain and economic burden to patients. At present, most implants on the market are made of pure titanium and titanium alloy materials, because titanium has good biocompatibility, bioinertness, high strength-to-weight ratio, relatively low elastic constant and excellent corrosion resistance compared to other metal materials. But at the same time, titanium and its alloy materials will also have some unsolvable problems. Some studies have measured the cumulative amount of titanium ions in micro-implants by inductively coupled plasma mass spectrometry detection, and studied the role of titanium ions in the expression of cytokines and receptors in microorganisms. It was found that the sensitivity of gingival epithelial cells in oral microorganisms was affected by free titanium ions, which also affected the process of monocyte infiltration and osteoclast differentiation, and it was speculated that titanium ions and peri-implantitis have a certain correlation. In addition, titanium may be immunogenic, causing some allergic patients to have type IV hypersensitivity reactions to metal implants. At the same time, it is generally believed that titanium alloy, as an inert material, has low surface bioactivity and cannot induce osteoblasts to adhere and proliferate to form bone integration in the short term. Therefore, under normal circumstances, it takes 3-6 months after the implant is implanted in the body before it can be used under weight. Poor bone integration may even cause the implant to loosen and fall off, affecting the long-term repair effect.
[0004] In order to expand the indications of implants, improve the success rate, shorten the treatment process, and speed up the time required for healing, scholars are committed to constructing new implant surface coatings to promote bone bonding on the implant surface. Among bioactive coatings, hydroxyapatite is a bioactive calcium phosphate ceramic whose chemical composition and crystal structure are similar to the minerals of natural bone and dentin. It is currently the most commonly used bone regeneration material. However, pure hydroxyapatite has poor wear resistance and fracture toughness, which cannot match the mechanical behavior of natural bone, hindering its clinical application as a coating material on the surface of implants. At the same time, its low strength easily leads to crack propagation and reduces its corrosion resistance. In this regard, a variety of hydroxyapatite-based nanocomposite coatings have been developed, including polymers (such as chitosan, hyaluronic acid, chitosan heparin) and carbon-based materials (such as graphene, graphene oxide, carbon nanotubes). Despite the higher mechanical properties, these reinforcements (such as carbon nanotubes, due to the presence of metal catalysts) usually weaken the biological properties of hydroxyapatite or have adverse effects on adjacent tissues. However, some reinforcing materials (such as ZrO2) will induce the decomposition of hydroxyapatite during the preparation process, resulting in a significant reduction in the biological activity of hydroxyapatite. In recent years, graphene-based materials have been widely used in various biological fields due to their unique structure and excellent mechanical and electrical properties, as well as good sterilization and biocompatibility. In particular, graphene oxide nanosheets have been widely used in various fields of biotechnology due to their very large specific surface area, easy chemical functionalization, and good biocompatibility. This makes graphene oxide an attractive and promising nanoscale reinforcing filler in biocomposites. At the same time, in recent years, more and more research work has been devoted to the preparation of graphene or its derivatives to enhance HA biocomposites. There have been reports in the literature on the incorporation of graphene or its derivatives into hydroxyapatite composites, using in-situ synthesis methods, biomimetic mineralization processes, spark plasma sintering technology, etc. However, these technologies have high preparation costs and require a long time, and are not suitable for the modification of the surface of oral implants. At present, no researchers have studied hydroxyapatite-graphene oxide hybrid coatings that can load interleukin 4. Summary of the invention
[0005] The present invention overcomes the defects of the prior art and provides a graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method and application thereof.
[0006] This invention is the first to evaluate the regulatory effect of HA / GO / IL-4 coating materials on macrophage polarization in vitro from an immunological perspective, to study the effect of the induced immune microenvironment on the osteogenic differentiation of bone marrow stem cells, and to verify the osteogenic properties of the coating materials in vivo.
[0007] The technical solution of the present invention is as follows
[0008] A method for preparing a graphene oxide GO / hydroxyapatite HA / IL-4 implant coating, in which a hydroxyapatite and graphene oxide mixed implant coating with sustained-release IL-4 was constructed on a titanium surface by an electrochemical method, and a relatively complete characterization test was performed on it.
[0009] The specific steps include:
[0010] (1) Preparation of coating:
[0011] The titanium sheet was polished and the edge was ground, then ultrasonicated in acetone, anhydrous ethanol, deionized water, and finally stored in anhydrous ethanol;
[0012] (2) Preparation of electrolyte:
[0013] The solution was stirred continuously with a magnetic stirrer at 36-37°C to uniformly distribute 4-4.5 mg / ml nano-hydroxyapatite powder in anhydrous ethanol, and then 0.8-0.85 ml of 5-5.5 mg / ml graphene oxide solution was slowly added dropwise, and stirring was continued for 2-3 hours. Finally, the pH value of the electrolyte was adjusted with nitric acid.
[0014] (3) Preparation of composite coating:
[0015] The hydroxyapatite / graphene oxide electrolyte obtained in step (2) was placed in an electrolytic bath at 36-37°C for electrochemical deposition, with continuous stirring at 30-31V, 0.8-0.9mA / cm 2 Deposition is performed under a constant voltage and current for 2 to 2.5 minutes; finally, the hydroxyapatite / graphene oxide composite coating is obtained by natural drying at room temperature;
[0016] (4) Adsorption of cytokines:
[0017] Recombinant mouse IL-4 is dissolved in deionized water at a concentration of 2 to 2.1 μg / ml, and the hydroxyapatite / graphene oxide composite coating obtained in step (3) is immersed in the IL-4 solution in the dark for 24 to 48 hours, frozen at -20 to 18°C overnight, and freeze-dried for 20 to 24 hours. Finally, the non-adsorbed IL-4 is washed away with PBS to obtain hydroxyapatite / graphene oxide / interleukin-4.
[0018] In the above method, in step (2), the pH value is 3.0 to 4.0.
[0019] In the above method, in step (3), in the electrolytic cell, the anode is a graphite electrode and the cathode is a titanium substrate.
[0020] In the above method, in step (4), the solvent of the IL-4 solution is sterile deionized water.
[0021] A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating. Hydroxyapatite and graphene oxide are combined to form an implant surface coating material, and then IL-4 is adsorbed through a high specific surface area and slowly and continuously released, so that while promoting bone differentiation of bone marrow stem cells, macrophages can be intervened in the polarization of macrophages toward the M2 direction, accelerating the formation of implant bone bonding in vivo and promoting osteogenesis. When a single-lens reflex camera is used for macroscopic observation, the coating surface is highly saturated milky white, and the material is evenly distributed. Further observation by scanning electron microscopy shows that the graphene oxide and hydroxyapatite coatings are uniform, smooth and dense under low magnification, and there are fine cracks on the surface; more obvious multi-layered large "coral" cracks can be seen under high magnification, which may be due to the rapid sublimation of deionized water in the interleukin-4 solution during the freeze-drying process, causing the lower graphene oxide layer to break. In addition, clustered circular protein-like structures can be observed on the surface, indicating that the hydroxyapatite / graphene oxide / interleukin-4 composite system has a good adsorption capacity for interleukin-4.
[0022] A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating is used in implant manufacturing.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] In the present invention, hydroxyapatite and graphene oxide can be combined to form an implant surface coating material, and then an appropriate amount of IL-4 can be adsorbed through a high specific surface area and slowly and continuously released, so that while promoting bone differentiation of bone marrow stem cells, macrophages can be intervened in the polarization of macrophages toward M2, accelerating the formation of implant bone integration in the body and promoting osteogenesis. The application of GO / HA / IL-4 coating makes implants more widely indicated, improves the success rate, shortens the treatment process, and accelerates the time required for healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of graphene oxide GO / hydroxyapatite HA / IL-4 implant coating of the present invention;
[0026] Figure 2 is a preparation flow chart of the method of the present invention;
[0027] Figure 3 This is a picture of an implant loaded with a composite coating according to the method of the present invention;
[0028] Figure 4 The scanning electron microscope images of each group of coatings;
[0029] Figure 5 The comparison results of the hydrophilicity test of each group of coatings are shown;
[0030] Figure 6 X-ray photoelectron spectra of the coating surfaces of each group;
[0031] Figure 7 is the X-ray diffraction energy spectrum of each group of coatings;
[0032] Figure 8 Raman spectra of each group of coatings;
[0033] Fig. 9 This is the X-ray energy dispersion spectrum of hydroxyapatite / graphene oxide / interleukin-4 composite coating;
[0034] Fig.10 The two-dimensional and three-dimensional surface microstructures of each group of coatings under atomic force microscopy;
[0035] Fig.11 Comparison of absorbance values of the coating before and after being immersed in PBS for 14 days;
[0036] Fig.12 Comparison of the adsorption capacity of coating proteins;
[0037] Fig.13 ELISA results show the cumulative release of IL-4 on Ti and HA / GO surfaces;
[0038] Fig.14 To image the IL-4 protein bound to FITC on Ti and HA / GO / IL-4 surfaces at 0.5, 1, 3, 5, 7, and 9 days, showing the adsorption and release of IL-4 on Ti and HA / GO surfaces;
[0039] Fig.15 The cell proliferation of mouse embryonic osteoblast precursor cells after co-culture with each group of coatings;
[0040] Fig.16 DAPI staining observation of mouse embryonic osteoblast precursor cells after co-culture with each group of coatings;
[0041] Fig.17 The Calcein-AM / PI staining results of mouse embryonic osteoblast precursor cells co-cultured with each group of coatings;
[0042] Fig.18 The results of Calcein-AM / PI staining analysis of mouse embryonic osteoblast precursor cells co-cultured with each group of coatings;
[0043] Fig.19 The scanning electron micrographs of mouse embryonic osteoblast precursor cell adhesion on the coating surface of each group;
[0044] Fig. 20 The scanning electron micrographs of macrophage cell adhesion on the coating surface of each group;
[0045] Fig.21 The morphology of mouse embryonic osteoblast precursor cells cultured in the conditioned medium of each group of coated macrophages for 24 hours;
[0046] Fig. 22 The migration ability of mouse embryonic osteoblast precursor cells in the conditioned medium of each group of coated macrophages. DETAILED DESCRIPTION
[0047] The following description combines specific illustrations to explain the technical solution so as to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and similar generalized embodiments made by ordinary technicians in the field without creative work are all within the scope of protection of the present invention.
[0048] Example 1
[0049] The flow chart of this embodiment is as follows Figure 2 shown.
[0050] A. Preparation of coating:
[0051] A circular titanium sheet of Φ1cm*0.1cm in size was polished and the edges were ground with #600-#1200 water-grit sandpaper, and then ultrasonically cleaned in acetone at 40KHz for 30 minutes, ultrasonically cleaned in anhydrous ethanol at 40KHz for 30 minutes, and ultrasonically cleaned in deionized water at 40KHz for 15 minutes, and finally stored in anhydrous ethanol.
[0052] B. Preparation of electrolyte:
[0053] The mixture was stirred continuously for 3 h at 37 °C with a magnetic stirrer at a speed of 180 r / min, so that 200 mg of nano-hydroxyapatite powder was evenly distributed in 50 ml of anhydrous ethanol. Then, 0.8 ml of 5 mg / ml graphene oxide solution was slowly added dropwise, and magnetic stirring was continued at 37 °C for 3 h. Finally, nitric acid (HNO3) was used to adjust the pH value of the electrolyte (pH = 3.0-4.0).
[0054] C. Preparation of composite coating:
[0055] The hydroxyapatite / graphene oxide electrolyte was placed in an electrolytic cell at 37°C for electrochemical deposition, with a magnetic stirrer continuously stirring at a speed of 180 r / min, and deposited for 2 min at a constant voltage and current of 30 V and 0.8 mA / cm2. Finally, the hydroxyapatite / graphene oxide composite coating was obtained by natural drying at room temperature for 24 h.
[0056] D. Adsorption of cytokines: Recombinant mouse IL-4 (interleukin 4) was dissolved in deionized water at a concentration of 2 μg / ml. The hydroxyapatite-graphene oxide sample was immersed in the IL-4 solution in the dark for 24 h, frozen at -20°C overnight, and freeze-dried for 1 day. Finally, the non-adsorbed IL-4 was washed away with PBS to obtain hydroxyapatite / graphene oxide / interleukin-4.
[0057] In this embodiment, the implant image loaded with the composite coating is as follows: Figure 3 The coating scanning electron microscopy image is shown in Figure 4 As shown. In this embodiment, hydroxyapatite and graphene oxide are combined to form an implant surface coating material, and then IL-4 is adsorbed through a high specific surface area and released slowly and continuously, so that while promoting bone differentiation of bone marrow stem cells, it can intervene in the polarization of macrophages in the direction of M2, accelerate the formation of bone bonding of the implant in the body, and promote osteogenesis. When using a SLR camera for macroscopic observation, the coating surface is highly saturated milky white, and the material is evenly distributed. Further observation by scanning electron microscopy shows that the graphene oxide and hydroxyapatite coatings are uniform, smooth and dense under low magnification, with fine cracks on the surface; more obvious multi-layered large "coral"-like cracks can be seen under high magnification, which may be due to the rapid sublimation of deionized water in the interleukin-4 solution during the freeze-drying process, causing the lower graphene oxide layer to break. In addition, clustered circular protein-like structures can be observed on the surface, indicating that the hydroxyapatite / graphene oxide / interleukin-4 composite system has a good adsorption capacity for interleukin-4 (specifically, Figure 4 shown).
[0058] Example 2
[0059] 1. Detection and characterization of physical and chemical properties
[0060] A single-lens reflex camera and a scanning electron microscope were used to observe the surface morphology of each group. X-ray energy dispersion spectroscopy was used to analyze the elements and types of each group of samples. X-ray photoelectron spectrometer was used to quantitatively analyze the elements on the coating surface. X-ray diffractometer was used to determine the phase composition of each group of samples. Raman spectroscopy was used to determine the chemical groups in the coating. A contact angle meter was used to measure the static contact angle of deionized water at 1s and 30s to evaluate the hydrophilicity of the coating surface. Atomic force microscopy was used to measure the surface roughness and morphology.
[0061] 2. Sustained release of IL-4
[0062] 2.1. Immerse the coating loaded with IL-4 in a 24-well plate containing 1 mL of PBS and incubate at 37°C. Collect the supernatant at specific time points and replenish fresh PBS in the 24-well plate. According to the manufacturer's instructions, use an ELISA kit to quantify the IL-4 content in the supernatant. Calculate the concentration using the standard curve formula and determine the cumulative release of IL-4.
[0063] 2.2. Bind fluorescein isothiocyanate to IL-4 protein to visually display IL-4
[0064] Loading and release. N-hydroxysuccinimide-fluorescein isothiocyanate was reacted with the original IL-4 protein according to the manufacturer's instructions. Then FITC-conjugated IL-4 was loaded onto the material surface following the same procedure as above. Fluorescence microscopy was used to capture the residues of FITC-labeled IL-4 on the material surface at specific time points.
[0065] 3. Cell biocompatibility
[0066] The coating was sterilized by ultraviolet light in a clean bench for 2 h, rinsed with PBS and placed in a cell culture incubator for 10 min. Mouse embryonic osteoblast precursor cell suspension was cultured at 5 × 10 4 The density of 1000 / ml was inoculated on the surface of each group of samples and placed in a constant temperature incubator. After 10 minutes, complete culture medium was added to 1 ml, and the medium was changed every other day. After culturing for 4 days and 7 days, the absorbance at 450nm wavelength was measured using a microplate reader according to the instructions of the CCK8 kit to evaluate the effect of the material on cell proliferation. The test was repeated 3 times in each group. After culturing for 4 days and 7 days, DAPI staining was used to directly observe the proliferation of mouse embryonic osteoblast precursor cells and macrophages on the surface of each group of coatings under a fluorescent inverted microscope. In order to study the effect of different sample coatings on the growth state of mouse embryonic osteoblast precursor cells, mouse embryonic osteoblast precursor cells were co-cultured with each group, and Calcein-AM / PI double staining was performed on the 1st and 4th days, and fluorescent images were taken using a fluorescent inverted microscope. The number of live and dead cells was quantitatively analyzed using Image J software.
[0067] Observation of cell morphology and adhesion: After 4 days of culture, rinse once with PBS, fix in 2.5% glutaraldehyde fixative precooled at 4°C overnight in a 4°C refrigerator. On the second day, wash twice with PBS for 10 minutes each time, dehydrate in an ethanol solution for 15 minutes, and finally store in tert-butanol solution and refrigerate at 4°C overnight. On the third day, freeze-dry the sample at -88°C, and observe the cell morphology and adhesion by scanning electron microscopy.
[0068] 4. Biological response of mouse embryonic osteoblast precursor cells to macrophages
[0069] The co-culture model was used to evaluate the biological response of mouse embryonic osteoblast precursor cells to macrophages. Mouse embryonic osteoblast precursor cells were cultured in macrophage conditioned medium (mixed with macrophage culture supernatant and complete culture medium at a ratio of 1:2). Macrophages were cultured in the conditioned medium on different groups of materials for 24 hours, stained with FITC for 40 minutes, stained with DAPI for 10 minutes, and then photographed by inverted fluorescence microscopy.
[0070] 5. Effects of macrophage-conditioned medium on the migration of mouse embryonic osteoblast precursor cells
[0071] The scratch test was used to detect the effect of mouse embryonic osteoblast precursor cells on migration in a co-culture environment. Before the scratch test, five horizontal lines were drawn on the back of a 6-well plate with a marker pen as a mark. Mouse embryonic osteoblast precursor cells of passages 3-5 were taken and cultured in a 6-well plate at 2×10 5 Inoculate cells at a density of 100 / well and observe the cells the next day. If the cell density reaches about 80%, replace the original culture medium with serum-free culture medium to starve the cells for 12 hours. Use a 200μL pipette tip to vertically draw a cell-free strip on the bottom of the plate, wash the remaining cell debris and dead cells with PBS, add culture medium and then add the corresponding EXOs and LPS. Immediately after adding the culture medium, take a picture under a microscope as the migration distance of 0h, and take pictures again after 12h of culture. Note that the picture is taken at the same position as the previous picture.
[0072] 6. Statistical analysis
[0073] SPSS27.0 was used for statistical analysis of the data, and GraphPad Prism 10.1.2 software and Origin 2021 were used for graphical analysis. X±s was used to represent quantitative data. One-way analysis of variance was used for comparison between groups (Bonferroni method or Tamhane'T2 method was used for post hoc comparison). For two-sided tests, P<0.05 was considered statistically significant. All the above experiments were repeated 3 times.
[0074] The results of the coating physical and chemical properties test are as follows: Figures 4 to 10 shown.
[0075] in Figure 4The following are scanning electron micrographs of the coatings in each group. Scanning electron microscopy revealed that the hydroxyapatite-graphene oxide group and the hydroxyapatite / graphene oxide / interleukin-4 group had a unique nanoscale wrinkled structure of graphene oxide on the surface of the base, which is the same as observed in previous studies. This nanoscale wrinkled structure can increase the surface area of cell contact and promote biological behaviors such as cell adhesion. In addition, under a high-power electron microscope, obvious cracks can be seen on the surface of the hydroxyapatite / graphene oxide / interleukin-4 group, which is in the shape of multi-layered large "corals". This structure may be due to the rapid sublimation of deionized water in IL-4 during the freeze-drying process, resulting in the fracture of the lower graphene oxide. Compared with the hydroxyapatite-graphene oxide group, many clustered circular protein-like structures can be seen on the surface of the hydroxyapatite / graphene oxide / interleukin-4 group, which indirectly indicates the successful adsorption of IL-4. Fig. 9 In the X-ray energy dispersion spectrum analysis, the hydroxyapatite / graphene oxide / interleukin-4 coating contains O, C, P, and Ca elements, which are evenly distributed in the micro-area, and no titanium content is detected; Figure 7 In the X-ray diffraction patterns, C, O and Ti were detected on the surface of the pure titanium group and the pure titanium-IL-4 group, while no titanium was detected on the surface of the hydroxyapatite / graphene oxide / IL-4 group. Both results prove that the coating of the hydroxyapatite / graphene oxide / IL-4 composite coating is comprehensive and relatively dense. Figure 6 In the X-ray photoelectron spectrum, it was found that Ca2p, P2p and other element peaks were detected in the hydroxyapatite / graphene oxide / interleukin-4 group, which are all components of hydroxyapatite and Figure 8 The characteristic peaks of graphene oxide were seen in the Raman spectrum, proving the deposition of graphene oxide.
[0076] Coating stability Fig.11 There is no statistically significant difference between the absorbance of the coating after immersion in PBS for 14 days and the initial absorbance of PBS, which verifies the stability of the HA / GO coating.
[0077] The test results of coating loading and sustained release of IL-4 are as follows Figure 12 to Figure 14 shown. Fig.13 ELISA results show the cumulative release rate of IL-4 on Ti and HA / GO surfaces. In contrast, more than 70% of IL-4 in the pure titanium group was released on the first day, showing an initial burst release. Therefore, compared with pure titanium, this coating has a sustained release effect. This conclusion was also confirmed by comparing the fluorescence intensity of different surfaces at specific time points. Fig.14The IL-4 protein on the Ti and HA / GO / IL-4 surfaces was imaged with FITC binding at days 0.5, 1, 3, 5, 7, and 9, showing the adsorption and release of IL-4 on the Ti and HA / GO surfaces. HA / GO adsorbed more protein than Ti on day 0, and after 3 days, IL-4 on the pure titanium surface was almost non-existent, while the release of IL-4 loaded on the HA / GO surface lasted for nearly 9 days. Therefore, GO coating not only increased the loading of IL-4, but also maintained the release of IL-4.
[0078] Fig.12 For the comparison of the protein adsorption capacity of the coating, HA / GO has a nanoscale surface compared to pure titanium surface, which provides additional surface area for protein loading. In addition, due to hydrophobic interactions, electrostatic forces and hydrogen bonds, the HA / GO coating promotes interaction with proteins, thereby promoting sustained release.
[0079] The biocompatibility test results of the coating are as follows Figure 15 to Figure 19 shown.
[0080] The bone integration process of implants involves multiple cells such as bone tissue cells and immune cells. Among them, osteoblasts are the main functional cells for bone formation and are responsible for the synthesis, secretion and mineralization of bone matrix. Therefore, this study selected P3 generation mouse embryonic osteoblast precursor cells for in vitro cell experiments, and studied the effects of different material surfaces on the proliferation, growth and adhesion of mouse embryonic osteoblast precursor cells by co-culturing with four groups of composite coatings. Fig.15 The CCK-8 test results showed that on the fourth day, the OD value of the pure titanium-interleukin-4 group was higher than that of the Ti group (P<0.001), and the OD value of the hydroxyapatite / graphene oxide / interleukin-4 group was higher than that of the other three groups (P<0.01). A previous experiment showed that IL-4 loading can promote the proliferation and migration of mouse bone marrow mesenchymal stem cells, and the results of this study are basically consistent with it. Figure 5In the contact angle test results, the contact angles of the pure titanium-interleukin-4 group at 1s and 30s were greater than those of the pure titanium group (P<0.001), and the hydroxyapatite / graphene oxide / interleukin-4 group was greater than that of the hydroxyapatite-graphene oxide group (P<0.001), indicating that the loading of IL-4 would affect the hydrophilicity of the material itself. This may be due to the formation of a thin film of adsorbed protein on the substrate surface after freeze-drying of the IL-4 solution, which affects the contact area of the material and thus the hydrophilicity. There was no significant change in the Raman spectrum of the coating material before and after loading IL-4, mainly because IL-4 binds to the surface of the material by physical adsorption rather than chemical binding. Therefore, the interaction between IL-4 and the substrate material is relatively weak, and the loading concentration is low, so that the presence of IL-4 will not significantly affect the Raman characteristics of the material. Studies have shown that improving the hydrophilicity of the material not only inhibits the inflammatory response, but also has a positive effect on bone formation. In this study, although the loading of IL-4 sacrificed some of the hydrophilicity, its cell proliferation-promoting effect was far greater than that of the coating without IL-4. Therefore, whether the effect of IL-4 on hydrophilicity will reduce osteogenic activity requires further experimental verification. In addition, the contact angles of the hydroxyapatite / graphene oxide / interleukin-4 group at 1s and 30s were smaller than those of the pure titanium-interleukin-4 group (P<0.001), indicating that the addition of the hydroxyapatite-graphene oxide composite material greatly increased the hydrophilicity of the coating. The hydrophilic surface of the coating can promote the osteogenesis of osteoblasts and bone marrow mesenchymal stem cells both in vitro and in vivo. Some scholars verified that the hydroxyapatite-graphene oxide composite coating can promote the proliferation and adhesion of bone marrow mesenchymal stem cells and RAW264.7 cells by co-culturing mouse bone marrow mesenchymal stem cells and RAW264.7 macrophages in vitro. This study also found that on the seventh day of culture, the OD value of the hydroxyapatite / graphene oxide / interleukin-4 group was higher than that of the Ti group (P<0.01) and the pure titanium-interleukin-4 group (P<0.05). The addition of hydroxyapatite-graphene oxide composite material promoted the proliferation of osteoblasts. Fig.16 and Fig.17 Nuclear staining and Calcein-AM / PI staining were used to more intuitively display the number of cell adhesion and survival status of each group of coatings. Fig.19 and Fig. 20 The results of cell scanning electron microscopy showed that compared with the Ti group, the mouse embryonic osteoblast precursor cells and macrophages in the pure titanium-interleukin-4 group and the hydroxyapatite / graphene oxide / interleukin-4 group extended more pseudopodia, had closer cell-to-cell connections, and had a larger adhesion area than the hydroxyapatite-graphene oxide group.
[0081] The biological response of mouse bone marrow mesenchymal stem cells to macrophages Figure 21-22 shown.
[0082] After 24 h, cells cultured in the conditioned medium of each group stretched well, but compared with cells cultured in the conditioned medium of the pure titanium group, cells cultured in the conditioned medium of the Ti / IL-4 and HA / GO / IL-4 groups stretched more and had larger diffusion areas marked by fluorescent actin ( Fig.21 The results showed that the conditioned medium of Ti / IL-4 and HA / GO / IL-4 groups promoted the expansion of BMSCs. In addition, BMSCs migrated due to the induction of conditioned medium ( Fig. 22 ). The results showed that the four groups of macrophage conditioned medium promoted the migration of BMSCs at 24h, and the migration of cells cultured in the conditioned medium of the HA / GO / IL-4 group was more obvious. Activated macrophages promote the migration and homing of BMSCs, which is mainly achieved by secreting chemokines such as CCL2, CXCL8 and SDF-1.
[0083] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
Claims
1. A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method thereof, characterized in that: The steps include: (1) Preparation of coating: The titanium sheet was polished and the edge was ground, then ultrasonicated in acetone, anhydrous ethanol, deionized water, and finally stored in anhydrous ethanol; (2) Preparation of electrolyte: Under continuous stirring at 36-37 °C, 4-4.5 mg / ml nano-hydroxyapatite powder was evenly distributed in anhydrous ethanol, and then 0.8-0.85 ml of 5-5.5 mg / ml graphene oxide solution was slowly added dropwise, and stirring was continued. Finally, nitric acid was used to adjust the pH value of the electrolyte. (3) Preparation of composite coating: The hydroxyapatite / graphene oxide electrolyte obtained in step (2) was placed in an electrolytic bath at 36-37 °C for electrochemical deposition with continuous stirring at 30-31 V, 0.8-0.9 mA / cm 2 Deposition under constant voltage and current; finally, natural drying at room temperature to obtain a hydroxyapatite / graphene oxide composite coating; (4) Adsorption of cytokines: Recombinant mouse IL-4 was dissolved in deionized water at a concentration of 2-2.1 μg / ml. The hydroxyapatite / graphene oxide composite coating obtained in step (3) was immersed in the IL-4 solution in the dark, frozen at -20-18°C overnight, and freeze-dried for 20-24 hours. Finally, the non-adsorbed IL-4 was washed away with PBS to obtain hydroxyapatite / graphene oxide / interleukin-4.
2. A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method thereof as claimed in claim 1, characterized in that: In step (2), the pH value is 3.0-4.
0.
3. A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method thereof as claimed in claim 1, characterized in that: In step (2), the stirring time after adding the graphene oxide solution is continued for 2 to 3 hours.
4. A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method thereof as claimed in claim 1, characterized in that: In step (3), in the electrolytic cell, the anode is a graphite electrode and the cathode is a titanium substrate.
5. A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method thereof as claimed in claim 1, characterized in that: In step (3), the deposition time is 2 to 2.5 min.
6. A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method thereof as claimed in claim 1, characterized in that: In step (4), the solvent of the IL-4 solution is sterile deionized water.
7. A graphene oxide GO / hydroxyapatite HA / IL-4 implant coating and a preparation method thereof as claimed in claim 1, characterized in that: In step (4), the light-proof immersion time is 24 to 48 hours.
8. Graphene oxide GO / hydroxyapatite HA / IL-4 implant coating prepared by the preparation method according to any one of claims 1 to 7.
9. The graphene oxide GO / hydroxyapatite HA / IL-4 implant coating according to claim 8, characterized in that: Hydroxyapatite and graphene oxide are combined to form an implant surface coating material, which then adsorbs IL-4 through a high specific surface area and releases it slowly and continuously, thereby promoting the osteogenic differentiation of bone marrow stem cells while intervening in the polarization of macrophages in the M2 direction, accelerating the formation of implant bone integration in the body, and promoting osteogenesis; the coating surface is highly saturated milky white, and the material is evenly distributed; the graphene oxide and hydroxyapatite coating is uniform, smooth and dense, with fine cracks on the surface; under a high-power microscope, there are obvious multi-layer large "coral"-like cracks, and clustered circular protein-like structures can also be observed on the coating surface.
10. Application of the graphene oxide GO / hydroxyapatite HA / IL-4 implant coating according to claim 8 or 9 in implant manufacturing.